The Role of MIF in Type 1 and Type 2 Diabetes Mellitus - Sánchez-Zamora, Yuriko I. (Hindawi Publishing Corporation, 2014)
Autoimmunity and chronic low-grade inflammation are hallmarks of diabetes mellitus type one (T1DM) and type two (T2DM), respectively. Both processes are orchestrated by inflammatory cytokines, including the macrophage migration inhibitory factor (MIF). To date, MIF has been implicated in both types of diabetes; therefore, understanding the role of MIF could affect our understanding of the autoimmune or inflammatory responses that influence diabetic pathology. This review highlights our current knowledge about the involvement of MIF in both types of diabetes in the clinical environment and in experimental disease models.